Cross & Sampson - Patterson, James, 1947-; Sitts, Brian (Patterson, James. Alex Cross, 2026)
"Metro PD detective John Sampson stands in a crater in the middleof a DC street, calling in the bomb squad. "Dispatch, this is Sampson. Contact the FBI and the ATF. We've got a suspected terrorist attack here." In Chapel Hill, NC ... Alex Cross searches the apartment of a missing psychology grad student--his own son Damon. Has following in his famous father's footsteps made Damon a target?"--Provided by publisher.